OPTIMIZATION OF EDUCATION QUALITY IMPROVEMENT IN TARUS CHRISTIAN HIGH SCHOOL - Frans Beeh; Simon S. Sabon Ola; Basri K (Academic Journal of Educational Sciences, 2020)
This study aims to determine; 1) Planning, implementing and evaluating content standards at Tarus Christian High School, 2) Planning, implementing and evaluating process standards in Tarus Christian High School and 3) Planning, implementing and evaluating standards for educators and education personnel at Tarus Christian High School. This study used a qualitative approach. The research design used a case study conducted in tarus Christian high school. Discussion on content standards. In terms of implementation, the curriculum structure needs to be optimized, such as utilizing an additional time allocation policy of six to eight hours of lessons in learning activities at school. Standard process, for making syllabus and lesson plans must be done independently. The discipline of teachers and students must also be improved. An assessment of the learning process must be carried out. Determination of learning completeness must be based on the specified minimum completeness criteria. Supervision activities must often be carried out by school principals and supervisors. Minimum academic qualifications of diploma IV (D-IV) or undergraduate (S1) teachers. Permanent teachers from foundations who are paid according to the provincial minimum wage (UMP) which applies.